Exploring the Crossroads of Innate and Adaptive Immunity Against Mycobacterium Tuberculosis - Eden Sedarous; Dima Traboulsi; Heeral Dodhia; Katey Kwan; Suky Zheng; Venice Co (Canadian Journal for the Academic Mind)
This review examines the complex interactions between Mycobacterium tuberculosis and host immunity, with a focus on Mtb and immune evasion. Upon inhalation, Mtb infects alveolar macrophages, inhibiting phagosome-lysosome fusion to survive. Dendritic cells are later activated, driving CD4+ T cell differentiation and IFN-γ release to enhance macrophage bactericidal activity. Mtb may be sequestered in granulomas, which contain the infection but facilitates Mtbpersistence during latency. Further, cytotoxic T lymphocytes eliminate infected cells, while regulatory T cells modulate immunity. Overall, host immune responses must balance between pathogen control and tissue damage. Thus, Mtb’simmune evasion mechanisms pose a significant challenge for vaccine development and therapeutic intervention. Understanding these interactions is critical for uncovering novel strategies against Mtb infection and improving public health outcomes.